Phenolics and Lipid Antioxidants from Washingtonia robusta - H. El-Sayed, Nabil; M. Ammar, Nagwa; Y. Al-Okbi, Sahar; T. Bou-El-Kassem, Lamia; J. Mabry, Tom (Asian Journal of Chemistry, 2010)
Our phytochemical investigations of Washingtonia robusta Wendl. leaves detected the previously isolated flavonoids and, in addition, luteolin and its 7-O-glucoside, tricin 7-Oglucoside, isovitexin 3´-O-methyl ether, isoorientin 3´-O-methyl ether and p-hydroxybenzoic acid. The unsaponifiable material of the lipoidal fraction exhibited twenty hydrocarbons, four sterols, one triterpene and three fat-soluble vitamins, while the saponifiable portion contained thirteen saturated and unsaturated fatty acids. The different successive extracts were tested for their antioxidant activities. The aqueous methanolic extract showed 61% (AA) relative per cent inhibition, followed by the ether extract 52% while pet. ether, chloroform and methanol extracts exhibited the lowest inhibition at 13%, 10% and 8%, respectively. All compounds were separated and identified by chemical and physical spectroscopic analysis including acid hydrolysis, HPLC, GLC, 1H-NMR, 13C-NMR, COZY experiments, CMS and UV spectra.